Informality in Paraguay : Macro-Micro Evidence and Policy Implications - Vargas, Mauricio (IMF Working Papers; Working Paper ;, 2015)
Paraguay's economy features a high degree of informality. Based on different estimation approaches, informal activity represents more than half of total employment in Paraguay, a higher rate than those observed in its Latin American and the Caribbean peers. Theoretical and empirical considerations support the notion that regulations, enforcement policies, and government effectiveness are the ultimate determinants of informality. In all of these areas Paraguay performs weakly compared to regional peers. Using household and enterprise surveys, we find that Paraguay's informal sector absorbs the most vulnerable workers but affects negatively medium and large firms in the formal sector. DSGE model simulations suggest that the optimal combination of policies to reduce informality is not straightforward, and needs to reflect the specific circumstances and objectives of the country.